(untitled) (Universitas Medica, 2021)
The rapid intubation sequence is the method of choice for airway assurance in the emergency department, this procedure in addition to the passage of the orotracheal tube through the glottis consists of different steps which must be done in a thorough and sequential way to ensure the airway in the shortest possible time, with the least number of attempts and ideally without associated complications. Due to the importance of this topic, new recommendations have been given regarding each of the moments of this procedure, starting on indications and contraindications, techniques to the preparation and planning of the approach of the airway such as MACOCHA and HEAVEN mnemotechnics, the early use of vasopressors and crystalloids for patients at risk of hemodynamic deterioration , the use of different techniques for preoxygenation such as non-invasive mechanical ventilation or apneic preoxygenation. In addition, we must individualize each patient when choosing each drug either to premedicate, perform hypnosis or muscle relaxation. Additionally, new techniques such as the use of ultrasonography to corroborate the proper positioning of the orotracheal tube and post-intubation care. All these topics will be addressed in this review